2016
DOI: 10.1111/1477-9552.12155
|View full text |Cite
|
Sign up to set email alerts
|

Farmer Participation, Entry and Exit Decisions in the Italian Crop Insurance Programme

Abstract: The factors affecting the demand for agricultural insurance in the USA have been extensively studied over the last two decades. However, the determinants of a farm's entry and exit decisions in the insurance market have received relatively little attention. Turnover in the insurance book of business is an important issue in most private and public crop insurance plans. Moreover, insurance markets in the EU are still largely under‐investigated. We investigate empirically the determinants of crop insurance parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 42 publications
5
82
0
1
Order By: Relevance
“…Our dataset provides yearly information on land size, altitude, farmers' age, diversification of farming activities, adoption of irrigation, and farms' revenue. We compute revenue variability as standard deviation of farms' revenue (over the entire period, 2004-2010), and expected premium per hectare by averaging across regions and farming systems the (crop-specific) total premia, as proposed in Santeramo et al (2016) and Goodwin (1993). 3 The variable proxies farming system-specific and region-specific levels of riskiness.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Our dataset provides yearly information on land size, altitude, farmers' age, diversification of farming activities, adoption of irrigation, and farms' revenue. We compute revenue variability as standard deviation of farms' revenue (over the entire period, 2004-2010), and expected premium per hectare by averaging across regions and farming systems the (crop-specific) total premia, as proposed in Santeramo et al (2016) and Goodwin (1993). 3 The variable proxies farming system-specific and region-specific levels of riskiness.…”
Section: Datamentioning
confidence: 99%
“…A vast number of studies have analyzed the determinants of participation in crop insurance programs (Skees and Reed 1986;Goodwin 1993;Smith and Goodwin 1996;Sherrick et al 2004;Walters et al 2014;Tolhurst and Ker 2015;Menapace et al 2016), the dynamics of subsidized crop insurance programs (Coble and Barnett 2013), and the potential effects of innovative contracts (Maestro et al 2016). Santeramo et al (2016) analyzed the drivers for entering and exiting from the crop insurance market. However, existing research, with few exceptions (e.g., Cole, Stein, and Tobacman 2014;Santeramo 2018), has stopped short of providing a deeper investigation into the role of experience on participation in crop insurance programs.…”
mentioning
confidence: 99%
“…In such a case, losses and premium rates eventually increase and more farmers drive out from the insurance market. Santeramo et al (2016) argued that the expected loss ratio plays a significant role in the farmer's participation to insurance program and demonstrated that contrary to prior expectations, higher expected loss ratios correspond to a lower likelihood of participation and to a more probability of exit. Although these two problems and correlated risks are not unique to crop insurance but addressing these issues for crop insurance is more costly due to the high costs of monitoring agricultural production (Goodwin and Smith, 1995).…”
Section: Introductionmentioning
confidence: 88%
“…Coble et al, 1996), asymmetric information (e.g. Zilberman, 2008 andGlauber et al, 2002) or farmers characteristics (Santeramo et al, 2016a). Low insurance demand is often due to the infrequency of events and the high premiums derived under the actuarial principles leading market-based insurance, which discourage farmers to pay the premiums every year when indemnities are seldom received (Mahul and Stutley, 2010).…”
Section: Agricultural Insurance System Sustainability and Risk Predicmentioning
confidence: 99%